Utilization of Crumb Rubber as An Additive to Asphalt Mixture in Asphalt Concrete (AC-BC) Pavement - Ramadhan, Taufik Hibatullah; Mayuni, Sitii; Sumiyattinah, Sumiyattinah (Jurnal Teknik Sipil, 2024)
Highways are crucial for smooth and safe travel but often face damage and potholes. To enhance asphalt quality, this study explored the addition of crumb rubber, derived from recycled tires, to the Asphalt Concrete-Binder Course (AC-BC) mixture. The aim was to assess the impact of crumb rubber on asphalt properties based on the 2018 Revision 2 Bina Marga Specification. The research, conducted at the Highway Laboratory, Tanjungpura University, utilized an experimental method. Coarse aggregates (stones 1-1 and 05) from Peniraman, Mempawah Regency, and fine aggregates (sand and stone ash) from Pontianak and PT Sema were used"”asphalt pen. 60/70 was employed, and test specimens were prepared with varying asphalt contents of 5% to 7%, finding an optimum content of 6.1%. Crumb rubber was added in varying amounts (0%, 2%, 4%, 6%, 8%, and 10%) at this optimum content. Variations of 0%, 2%, 4%, 6%, and 8% met the Marshall parameters, with 4% yielding the highest stability at 948.48 kg, improving stability by 5.07% and flow by 16.30% compared to mixtures without crumb rubber. The study suggests further research on pavement types to evaluate crumb rubber's broader applicability.Keywords: Asphalt Concrete - Binder Course (AC - BC), Crumb Rubber, Asphalt, Marshall Test, An Additive to Asphalt Mixture